Prevalence of anaemia and its associated factors among HIV-infected adults at the time of ART initiation at Debre Markos Comprehensive Specialized Hospital, Northwest Ethiopia: a retrospective cross-sectional study - Agazhe Aemro; Belayneh Shetie Workneh; Enyew Getaneh Mekonen; Mulugeta Wassie; Basazinew Chekol (BMJ Open)
Objective The aim of this study was to assess the prevalence of anaemia and its associated factors at the time of antiretroviral therapy (ART) initiation among HIV-infected adults at Debre Markos Comprehensive Specialized Hospital.Methods An institution-based retrospective cross-sectional study was conducted among 473 patients’ charts enrolled from 2014 to 2018 at Debre Markos Comprehensive Specialized Hospital. Patients’ chart numbers were selected from the computer using a simple random sampling technique. Data were entered using Epi Info V.7.2.2.6 and analysed with Stata V.14.0. Anaemia prevalence at the time of ART initiation was computed and described using frequency tables. To identify factors for anaemia, bivariate and multivariate logistic regression models were fitted. Model fitness was checked using the Hosmer-Lemeshow goodness-of-fit test.Results From 473 patients’ charts, 468 charts were included in the analysis, and a total of 164 anaemia cases were recorded. The overall prevalence of anaemia among HIV-infected adults at the time of ART initiation was 35.04% (95% CI: 30.84% to 39.49%). After multivariate analysis, an increased risk of anaemia was seen among males (adjusted OR (AOR)=2.45; 95% CI: 1.51 to 3.98); those not attending formal education (AOR=2.38; 95% CI: 1.12 to 5.05); those who had baseline CD4+ T cell count ≤200 cells/mm3 (AOR=4.67; 95% CI: 2.78 to 7.85); had body mass index (BMI) <18.5 kg/m2 (AOR=2.43; 95% CI: 1.42 to 4.16) and had ambulatory/bedridden baseline functional status (AOR=2.69; 95% CI: 1.41 to 5.12).Conclusion The current study showed that a significant proportion of HIV-infected adults developed anaemia at the time of ART initiation. Hence, giving special attention to those who have not attended formal education, were males, had decreased baseline CD4+ T cell count, had lower BMI and patients with ambulatory/bedridden baseline functional status is crucial to reduce the health impact of anaemia. The result will provide insight into the development of new anaemia preventive strategies.